(untitled) (Journal of Asian Development Studies, 2024)
The risk is amplified by poverty, lack of education and social stigma. Transmission occurs mainly by unprotected sex, needle sharing, or mother-to-child - either during birth or breastfeeding. HIV’s pathogenic life cycle begins within the body, from initial CD4/co-receptor binding and cell entry to proviral DNA integration, host cell machinery replication, and immune response evasion. This chronic immune activation and CD4+ T cell depletion over time leads to immunodeficiency (AIDS) if left untreated. Antibody and viral load testing can confirm infection. Acute HIV symptoms resemble the flu, while later stages see opportunistic infections when immunity is compromised. Screening is essential for epidemiological research and exposure risk evaluation. In closing, this study aimed to evaluate HIV prevalence and associated factors among residents of DG Khan District, Pakistan, to help address challenges and better focus local prevention/treatment programs.